Ferroptosis: A Novel Therapeutic Target for Ischemia-Reperfusion Injury - Chen, Yunqing; Fan, Hongyan; Wang, Shijun; Tang, Guanmin; Zhai, Changlin; Shen, Liang (Frontiers in Cell and Developmental Biology, 2021)
Ischemia-reperfusion (I/R) injury is a major cause of cell death and organ damage in numerous pathological states, such as myocardial infarction, stoke and acute kidney injury. Nowadays, treatment methods for I/R injury remain limited. Ferroptosis, a new type of regulated cell death, which is characterized by iron overload and accumulation of lipid peroxidation, has been investigated in various diseases. A growing number of evidence has shown that there is a close association between ferroptosis and I/R injury. Ferroptosis is identified as a new therapeutic target for the management of I/R injury. This review summarizes the current status of ferroptosis and discusses the relationship between ferroptosis and I/R injury as well as potential treatment strategy targeting ferroptosis.